Ecology of Peltoperla arcuata and Tallaperla maria (Plecoptera: Peltoperlidae) at the Fernow Experimental Forest, Tucker County, West Virginia - Kevin A. Yokum; Ted R. Angradi; Donald C. Tarter (Psyche: A Journal of Entomology)
We examined the abundance, life history, and production of the stoneflies Peltoperla arcuata and Tallaperla maria (Plecoptera: Peltoperlidae) in four forested headwater streams at the Fernow Experimental Forest, Tucker County, West Virginia. Peltoperla arcuata was most abundant in the smallest watersheds (<100 ha), and was present at all sites. Tallaperla maria was most abundant in watersheds >200 hectares (ha), was restricted to sites with a base-flow alkalinity of >2 mg L-1 CaCO3, and was the dominant peltoperlid only at sites with an alkalinity >15 mg L-1. We conclude that water chemistry overrides stream size as a determinant of species-specific distribution of Fernow peltoperlids. Both taxa had semi-voltine life cycles with an 18-month naiadal period following a 6-month egg diapause. Emergence was during May-July for both species. Peltoperla arcuata had about 15 instars; T. maria had about 14 instars. Peltoperlid production was highest (509 mg m-2 y-1) in a 128 ha watershed where only P. arcuata was collected; P. arcuata production was lowest (17 mg m-2 y-1) in a 4th order stream (1536 ha). Taltaperla maria production was highest (271 m-2 y-1) in a 257 ha watershed partially underlain by limestone. Production across streams was higher for P. arcuata (205 mg m-2y-1) than for T. maria (91 mg m-2 y-1).